Supramolecular assembly of coumarin 7 with sulfobutylether-β-cyclodextrin for biomolecular applications - Gayathry, T. C.; Gaur, Monika; Mishra, Lopamudra; Mishra, Monalisa; Barooah, Nilotpal; Bhasikuttan, Achikanath C.; Mohanty, Jyotirmayee (Frontiers in Chemistry, 2023)
Coumarins, in general, exhibit a wide range of photophysical characteristics and are highly sensitive to their microenvironment, and, therefore, their fluorescence characteristics have attracted immense attention as sensors in chemical and biological systems. In the present study, the supramolecular interaction of a bichromophoric coumarin dye, namely, Coumarin 7 (C7) with sulfobutylether-β-cyclodextrin (SBE7βCD) macrocyclic host at different pH conditions has been investigated by using optical spectroscopic techniques such as absorption, steady-state and time-resolved emissions, and circular dichroism measurements and compared with that of βCD. Considerable enhancement in the fluorescence intensity and lifetime of C7 on complexation with SBE7βCD proposes that non-radiative processes like TICT behavior are strictly hindered due to the confinement in the host cavity experienced by the C7 dye. The increase in the rotational correlation time evaluated from the fluorescence anisotropy decay kinetics further confirms the formation of tightly bound inclusion complexes. The binding constant values reveal that the monocationic form of dye at pH 3 shows ∼3 times stronger interaction with SBE7βCD than the neutral form of dye at pH 7 due to strong electrostatic cation-anion interaction. SBE7βCD:C7 exhibits an improved photostability and an upward pKa shift of 0.4 unit compared to the contrasting downward pKa shift of 0.5 with the βCD. The enhanced fluorescence yield and increased photostability have been exploited for bioimaging applications, and better images were captured by staining the Drosophila fly gut with the SBE7βCD:C7 complex. The enhancement in the binding interaction and the emission intensity were found to be responsive to external stimuli such as small competitive binders or metal ions and nearly quantitative dissociation of the complex was demonstrated to release the dye and would find stimuli-responsive applications.